Surgical treatment of types I–IV hiatal hernias - A. M. Akhmatov; I. S. Tarbaev; D. I. Vasilevskii (Вестник хирургии имени И.И. Грекова)
The article presents modern ideas of types II–IV hiatal hernias as a variant of visceral anatomical abnormality. The latest techniques of surgical removal of hiatal hernias aimed at improving the results of surgical treatment are described in this article.